Two-dimensional thin film material composite film and preparation method and application thereof
By forming a composite film preparation method of combining layers and reinforcement layers on the surface of the two-dimensional film material and forming a laminated structure, the problem of insufficient mechanical strength of the two-dimensional film material is solved, the adhesion, tensile and bending performance is improved, and the practical application needs are met, breaking through the bottleneck of commercial development in the field of separation membranes is carried out.
Patent Information
- Application Number
- CN202311329495.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-13
- Publication Date
- 2025-04-15
AI Technical Summary
Two-dimensional film materials such as graphene are insufficient in adhesion and tensile strength, which is difficult to meet the application needs of processing, packaging and modular processing, and are prone to cracks during bending, reducing separation performance.
A method of preparing a two-dimensional film composite film is adopted. By forming a bonding layer and a reinforcement layer on the surface of the two-dimensional material film, a laminated structure is formed. The bonding layer connects the two-dimensional material film and the reinforcement layer. The reinforcement layer provides mechanical properties. The composite film formed includes a stacked two-dimensional material film, a bonding layer and a reinforcement layer.
The mechanical properties of the two-dimensional film composite film, including adhesion, stretching and bending properties, can meet the processing, packaging and modular processing requirements in actual applications, and maintain stability under different curvature states, breaking through the bottleneck of the practical application and commercialization of two-dimensional film materials in the field of separation membranes.
Smart Images

Figure CN119820931A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of material preparation, and in particular relates to a two-dimensional thin film material composite film and a preparation method and application thereof. Background Art
[0002] Given the atomic-level thickness, stable performance and controllable pore potential of two-dimensional thin film materials, two-dimensional thin film materials are gradually gaining favor as a viable platform for developing new membrane technologies. Theoretical calculations and proof-of-concept experiments have shown that nanoporous two-dimensional thin film material membranes can break through the "trade-off" effect between permeability and selectivity of traditional separation membranes and achieve ultrafast selective transport of specific substances. In addition, with the development of chemical vapor deposition (CVD) technology for growing two-dimensional thin film materials, great progress has been made in the roll-to-roll production of two-dimensional thin film material films, providing great opportunities for practical applications.
[0003] The practical application of two-dimensional thin film materials in membrane separation requires scalable preparation methods and can be easily integrated into devices. However, such atomically thin membranes have poor resistance to out-of-plane and in-plane deformation. For example, graphene thin film materials, on the one hand, the bending stiffness of single-layer graphene is very low (about 1-2Nm -2 ), it is impossible to build a stable three-dimensional structure in practical applications unless there is a supporting structure. On the other hand, in actual tensile tests, the peak tensile strain of self-supporting single-crystal monolayer graphene is only 5.8%, the minimum peak tensile strength before fracture is less than 150μN, and the tensile stiffness is extremely low, only about 350Nm -1 Therefore, the graphene membrane has poor resistance to deformation under stretching and bending. Therefore, it is still a challenge to prepare large-area nanoporous two-dimensional thin film materials with sufficient mechanical strength.
[0004] Many efforts have been made to address the problem of insufficient mechanical strength of two-dimensional thin film materials such as graphene in scalable manufacturing processes. The most commonly used method is to transfer graphene to a prefabricated porous support membrane by applying pressure to tighten the interface, but unexpected defects can occur due to poor contact between graphene and the support layer. Therefore, improving the quality of graphene films is crucial for scalable transfer. Polymers are deposited on graphene by electrospinning to form a highly porous substrate, but the interfacial contact area between cylindrical nanofibers and graphene films is limited, which poses a challenge to maintaining the integrity of the graphene-covered composite membrane. In order to prevent slip and delamination in practical applications, the adhesion between the graphene layer and the support layer needs to be further enhanced. The in-situ phase change technique of directly casting the polymer solution onto the graphene surface can form a porous polymer support that perfectly matches the graphene morphology. However, the highly flexible polymer layer is easily deformed, and the micrometer-sized pores in the polymer support cannot provide sufficient tensile strength. Therefore, using CVD, the performance of graphene films in membrane separations is still limited due to insufficient mechanical strength in terms of adhesion and tension.
[0005] In addition, designing and packaging the membrane into a suitable module is another key challenge. Looking back at the development of membrane science and technology, commercial membranes are generally rolled into spirally wound modules. It is inferred that large-area graphene membranes must also be packaged in modules by bending to a specific curvature for commercial use. However, current graphene composite membranes must be stabilized in a bent state by attaching to an additional porous substrate, and some small cracks may form during the bending process, which greatly reduces the separation performance of the graphene layer. Therefore, excellent bending performance is necessary for packaging processing and modularization in engineering applications.
[0006] To this end, the key to commercializing large-area two-dimensional thin film material separation membranes for engineering applications is to solve the problem of insufficient mechanical strength in adhesion and stretching of two-dimensional thin film materials during the preparation process and give them bending properties that meet the application requirements to withstand processing, packaging and modular handling. Specifically, an atomically selective two-dimensional thin film material should be composited onto a low-cost porous support structure that provides sufficient mechanical properties to allow the two-dimensional thin film material to be loaded into modules for practical applications. Suitable porous supports and composite methods between two-dimensional thin film materials and supports are crucial to solving the long-term development bottleneck of large-area two-dimensional membranes in practical separation applications. Summary of the invention
[0007] In order to solve the above-mentioned defects, the present invention provides a two-dimensional thin film material composite film and a preparation method and application thereof.
[0008] On the one hand, the present invention provides a two-dimensional thin film material composite film, including a stacked two-dimensional material film, a bonding layer and a reinforcement layer.
[0009] On the other hand, the present invention provides a method for preparing a two-dimensional thin film material composite membrane, comprising: S1, forming a bonding layer on the surface of a two-dimensional material film grown on a substrate to obtain a bonding layer / two-dimensional material film / substrate composite structure; S2, composite a reinforcing layer on the bonding layer of the bonding layer / two-dimensional material film / substrate composite structure to obtain a reinforcing layer / bonding layer / two-dimensional material film / substrate composite structure; and S3, removing the substrate in the reinforcing layer / bonding layer / two-dimensional material film / substrate composite structure to obtain the two-dimensional thin film material composite membrane.
[0010] Another aspect of the present invention provides an application of the above-mentioned two-dimensional thin film material composite membrane as a separation membrane.
[0011] The present invention solves the problem that the mechanical properties of the adhesion, stretching and bending of the composite membrane of two-dimensional thin film materials are difficult to meet the application requirements of processing, packaging and modular processing, breaking through the bottleneck of the practical application and commercial development of two-dimensional thin film materials in the field of separation membranes. A scalable composite membrane preparation method is adopted to introduce a low-cost reinforcement structure (non-woven fabric) into the composite membrane of large-area two-dimensional thin film materials, giving the nanoporous two-dimensional thin film material composite membrane high mechanical properties. Specifically, an atomically thick selective two-dimensional thin film material membrane is composited to a low-cost porous mechanical reinforcement structure, and the support structure provides sufficient mechanical properties to allow the atomic-level two-dimensional thin film material to be integrated into the module for practical application. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] The following drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present invention, but do not constitute a limitation of the present invention.
[0013] Figure 1 It is a process flow chart of preparing a two-dimensional thin film material composite membrane according to one embodiment of the present invention.
[0014] Figure 2 This is the Raman spectrum of the graphene side of the composite film of Example 1.
[0015] Figure 3 This is a scanning electron microscope image of the cross-sectional structure of the composite membrane of Example 1.
[0016] Figure 4 This is a scanning electron microscope image of the surface of one side of the composite film graphene of Example 1.
[0017] Figure 5 This is a scanning electron microscope image of one surface of the composite membrane nonwoven fabric of Example 1.
[0018] Figure 6 This is a graph showing the test results of the salt rejection performance of the composite membrane of Example 1.
[0019] Figure 7 This is a graph of the bubble point pressure test results of the composite membrane of Example 1.
[0020] Figure 8 This is a graph showing the mechanical peeling test results of the composite film of Example 1.
[0021] Fig. 9 This is a graph showing the mechanical tensile test results of the composite film of Example 1.
[0022] Fig.10 This is a demonstration effect diagram of the bending performance of the composite membrane of Example 1.
[0023] Fig.11 This is a demonstration effect diagram of the bending performance of the composite film of Example 1. DETAILED DESCRIPTION
[0024] The present invention is described in detail below in conjunction with specific implementation modes.
[0025] The two-dimensional thin film material composite film of the present invention comprises a stacked two-dimensional material film, a bonding layer and a reinforcement layer.
[0026] The two-dimensional material can be, but is not limited to, graphene, boron nitride, transition metal dichalcogenides, new polymers, framework materials, Mxene, etc. The two-dimensional material can be one layer or more layers, such as one layer of graphene film, or 2 layers of graphene film or more layers of graphene film, etc. Preferably, the thickness of the two-dimensional material film is 0.3nm-3nm.
[0027] The bonding layer serves to connect the two-dimensional material film and the reinforcement layer. Preferably, the bonding layer can be composited with the two-dimensional material film and the reinforcement layer at the same time, and the layers have good peel strength and maintain a stable bonding effect after bending and folding. The material used as the bonding layer may include, but is not limited to, one or more of organic materials, inorganic materials, and organic-inorganic hybrid materials. The organic material may be starch, cellulose, protein, plastic, rubber, synthetic fiber, etc. The inorganic material may be aluminum oxide, titanium oxide, zirconium oxide, carbon nanotubes, graphene, zeolite, boron nitride, siloxane, transition metal dichalcogenide, Mxene, etc. The organic-inorganic hybrid material may be silicone rubber, inorganic-organic framework, etc.
[0028] The thickness of the bonding layer may be 0.01-100 μm, preferably 5-30 μm.
[0029] The bonding layer may be a porous structure with a pore size between 0.01-50 μm, preferably 0.5-5 μm.
[0030] The role of the reinforcement layer is to improve the mechanical strength of the separation membrane and give it bending properties to withstand processing, packaging and modularization. The reinforcement layer includes but is not limited to structures or composite structures with anisotropic mechanical properties, such as fiber networks, composite structures embedded with fiber networks, non-woven fabrics, fabrics, etc. The material of the reinforcement layer can be polymers, natural materials such as cotton, linen, silk, etc.
[0031] The thickness of the reinforcement layer may be 1-1000 μm, preferably 50-500 μm.
[0032] The pore size of the reinforcement layer is between 0.05-1000 μm, preferably 5-50 μm.
[0033] The thickness of the two-dimensional thin film material composite film is 1-1000μm. The pore size is 0-10nm. The composite film has the ability to resist deformation under stretching and bending, and remains stable in different curvature states and after repeated bending processes.
[0034] like Figure 1 As shown, the preparation method of the two-dimensional thin film material composite membrane of the present invention includes: S1, forming a bonding layer on the surface of a two-dimensional material film grown on a substrate to obtain a bonding layer / two-dimensional material film / substrate composite structure; S2, compounding a reinforcing layer on the bonding layer of the bonding layer / two-dimensional material film / substrate composite structure to obtain a reinforcing layer / bonding layer / two-dimensional material film / substrate composite structure; and S3, removing the substrate in the reinforcing layer / bonding layer / two-dimensional material film / substrate composite structure to obtain the two-dimensional thin film material composite membrane.
[0035] In step S1, the bonding layer may be formed in any appropriate manner, including but not limited to physical and / or chemical methods, such as using pressure and temperature to induce film formation and / or bonding, deposition to induce film formation and / or bonding, self-assembly to induce film formation and / or bonding, phase transition to induce film formation and / or bonding, etc. Specifically, an appropriate film formation method may be selected according to factors such as the type of material and the nature of the film formation.
[0036] In step S2, the reinforcement layer is compounded to the surface of the bonding layer away from the two-dimensional material film to form a composite film. The method of compounding the reinforcement layer can be any appropriate method, including physical and chemical methods, such as using power drive, thermal drive, chemical bonding, etc.
[0037] In step S3, the substrate in the composite structure obtained in step S2 is removed to obtain a composite structure of a reinforcement layer / binding layer / two-dimensional material thin film, i.e., a two-dimensional thin film material composite film. The method for removing the substrate can be any appropriate method. An appropriate removal method can be selected according to the material of the substrate. For example, on a copper foil substrate, an etchant can be used to remove the copper foil. The substrate can also be removed by mechanical stripping, electrochemical bubbling, etc.
[0038] Step S3 may also include step S4. That is, in S4, a bonding layer / two-dimensional material film composite structure is obtained, which can be used as a transfer medium to transfer the two-dimensional material film to the composite structure again to form a reinforcing layer / bonding layer / two-dimensional material film / two-dimensional material film composite structure. Specifically, the reinforcing layer / bonding layer / two-dimensional material film composite structure can be bonded to the surface of the two-dimensional material film grown on the substrate to form a reinforcing layer bonding layer / two-dimensional material film 1 / two-dimensional material film 2 / substrate composite structure. Then remove the substrate in the composite structure. Removing the substrate can be any appropriate method, such as the method adopted in step S3, which will not be repeated.
[0039] The two-dimensional material film 2 transferred in step S4 may be the same as or different from the two-dimensional material film 1. For example, both may be graphene, one layer may be graphene and the other layer may be other two-dimensional materials, or both may be two-dimensional materials other than graphene.
[0040] Step S4 can be repeated multiple times to obtain a composite film comprising multiple layers of two-dimensional material thin films.
[0041] The two-dimensional thin film material composite membrane of the present invention can be used as a separation membrane. When used as a separation membrane, the composite membrane can be pore-formed according to specific conditions. Any appropriate pore-formation method can be used to obtain appropriate pores.
[0042] The present invention is further described below by specific examples. However, these examples are merely exemplary and do not constitute any limitation to the scope of the present invention. In the following examples and comparative examples, the reagents, materials and instruments used are all commercially available unless otherwise specified.
[0043] Example 1
[0044] In this embodiment, a double-layer graphene prepared by lamination transfer is used as a separation layer, an ultra-thin polyvinylidene fluoride (PVDF) bonding layer prepared by a phase transition method is used as a "binder" composited with graphene, and a non-woven fabric is selected as a mechanical reinforcement layer of the graphene composite membrane.
[0045] Stir DMAc and PVDF (10w) at 60℃ for 6h to dissolve into a uniform casting solution with a mass concentration of 25%. Pre-impregnate the G-Cu surface with the degassed casting solution to allow the casting solution to fully contact the graphene for 1h. Spin coat a layer of casting solution on the graphene surface (spin coater parameter settings: low speed 500r / 10s, high speed 4000 / 60s). Then use the NIPS method to form a film (conditions: room temperature, 500ml deionized water coagulation bath, 2h), dry at 60℃ for 0.5h, and then remove the copper substrate (specific method: completely etch the copper foil with 1mol / L sodium persulfate, and add a small amount of isopropanol to the etching solution), and then use deionized water to replace the etching solution to clean the composite structure until the conductivity of the cleaning solution reaches deionized water. The composite structure soaked in the above step is bonded to the surface of graphene grown on copper foil to obtain a "PVDF / graphene+graphene / copper foil" structure, and the composite structure layer soaked in ethanol is bonded to the PVDF side of the above structure to obtain a "non-woven fabric / PVDF+PVDF / graphene+graphene / copper foil" structure, which is sandwiched between two hot pressing plates and placed in a 110°C oven for hot pressing for 2 hours. The copper foil is removed using the copper substrate etching method in the above step to obtain a "double-layer graphene / PVDF / non-woven fabric" composite membrane.
[0046] The graphene structure was characterized by Raman spectrometer at 633 nm laser excitation wavelength. The surface and cross-sectional structure of the composite membrane were characterized by scanning electron microscopy at an acceleration voltage of 5.0 kV. The transfer quality of graphene in the composite membrane was evaluated by a diffusion cell liquid phase KCl permeation test. The test device was a diffusion cell with a single-side solvent of 5 ml and an effective test membrane area of 19.625 mm in diameter. 2 First, the composite membrane was pre-wetted, and anhydrous ethanol, 50% ethanol aqueous solution, and deionized water were added to both sides of the diffusion cell, and then discharged after magnetic stirring for 3 minutes. Then, 0.5 mol / L KCl solution was added to one side of the diffusion cell, and deionized water was added to the other side. The conductivity change of the deionized water side for 12 hours was recorded by the Mettler multi-parameter tester, and the integrity of the graphene layer was evaluated based on the conductivity change curve.
[0047] The integrity test of the samples was carried out using a bubble point pressure analyzer according to the GB / T 32361-2015 standard, and the bubble point pressure was used to illustrate the pressure bearing capacity of the membrane. The top and bottom surfaces of the membrane samples (width of about 10 mm and length of about 50 mm) were combined together by transparent tape and double-sided tape using a computer-controlled universal testing machine, and the interlayer adhesion between the graphene layer of the GCMs and the substrate was evaluated according to the standard T-peeling method. The membrane samples were subjected to tensile tests using a DHR-2 model rheometer, and the mechanical properties of the membrane samples were analyzed based on the stress-strain curve data of the samples. The test sample size was 40 mm in length, 0.2 mm in thickness, and 10 mm in width. The width of the sample was ensured to be consistent from top to bottom, and the tensile rate was set to 10 μm / s. The bending ability of the composite membrane was demonstrated by a demonstration experiment. The composite membrane was bent to different curvatures, and the morphology of the composite membrane was observed under a specific bending state, the mechanical flexibility and processability were evaluated, and the feasibility of rolling the membrane into a tube-type or spiral structure was determined. A self-made bending test equipment was used to carry out a reciprocating bending fatigue test on the membrane sample. The reciprocating bending rate of the instrument was 60 mm / s, the bending radius was 0.75 mm, and the number of reciprocating times was 10,000.
[0048] The membranes prepared by the method described above have relatively large surface areas and high integrity. Figure 2 The successfully prepared 10 cm × 10 cm graphene composite film and its Raman spectra at five different positions are shown. G and 2D peaks appear in the Raman spectrum, and the D peak is almost negligible (about 1350 cm -1 , corresponding defects). Figure 3 Scanning electron microscope image of the nonwoven surface structure, showing a connected fiber network. Figure 4 The composite membrane cross-section structure includes graphene, PVDF and non-woven fabric layers. Figure 5 The substrate is completely covered by graphene without any tears, cracks or holes, and the coverage is close to 100%. To further confirm the coverage of the graphene layer, a diffusion experiment of potassium chloride (KCl) on the wetted film was performed. Figure 6 The results showed that the conductivity did not change significantly, indicating that the coverage of graphene exceeded nearly 100%. These results indicate that a high-quality graphene layer has been successfully transferred to the target substrate.
[0049] Mechanical properties are crucial for extended preparation, packaging handling, module processing, and system integration. Therefore, the mechanical properties of composite films have been studied, mainly including compressive strength, tensile deformation, bending behavior, and interfacial adhesion. Figure 7 As shown in the figure, the average bubble point pressure of the composite membrane reaches more than 12 bar, and the rupture pressure of the graphene layer is about 10 bar, indicating that the composite membrane can withstand high pressure environment. Figure 8As shown in the figure, the peel strength of different layers of the composite film was studied. The results showed that the composite film had strong interfacial adhesion between the layers. When the peel strength reached 0.55N, the tape was separated from the graphene layer, and the graphene layer still maintained a high coverage. As the peel strength increased to 4.20N, part of the PVDF layer was peeled off, and it took 6.87N to completely peel the PVDF layer from the non-woven fabric layer. Fig. 9 As shown, the fracture stress, fracture strength and tensile stiffness of the composite film are 33.3MPa, 33.3N and 35011Nm respectively. -1 These results demonstrate the key role of the reinforcement structure in improving the tensile properties. Fig.10 As shown in Figure 2, the composite membrane can be bent into different curvatures without additional support under external forces and maintains shape stability in a specific bending state, indicating that the GCM has sufficient flexibility to resist large deformation. Fig.11 As shown in the figure, the composite film was bent back and forth 10,000 times, with a bending radius of about 15 mm and no plastic deformation. These results show that the mechanical properties of the composite film can meet practical applications and can be made into components by rolling into a spiral structure or a tubular structure to improve production efficiency in practical applications.
[0050] Test Case
[0051] Test 1
[0052] Combining pore making technology with this study will provide an effective solution to achieve the separation process from sub-nanometer to several nanometers. The present invention explores the water, steam and gas transmission capacity of the mechanically enhanced graphene composite membrane obtained in Example 1 after pore making to demonstrate the separation performance of the mechanically enhanced graphene separation membrane. As an example of preparing a mechanically enhanced large-area atomic-thick separation membrane, the present invention is expected to promote the practical application and long-term development of two-dimensional materials in the field of separation membranes.
[0053] The specific operation is to introduce nanopore structure into the composite membrane sample of Example 1. The composite membrane is etched by plasma in 10Pa argon atmosphere with 50W power for 40s to introduce nanopores on the surface of double-layer graphene. The sample is subjected to pressurized deionized water interception experiment using a stirred filter, and the effective area of the sample is measured to be 12.56cm 2 If no water is collected within 12 hours under a specific pressure, the membrane is impermeable to water. The water vapor transmission rate was obtained using a water vapor transmission rate analyzer. The equipment includes a low humidity chamber (lower part) and a high humidity chamber (upper part). The membrane is installed in the middle of the two chambers with an effective area of 7.06cm 2, in the presence of a humidity gradient of about 50% at 23°C, water vapor will diffuse through the membrane from the high humidity chamber to the low humidity chamber. The gas flux test was performed using a pore size analyzer, and the membrane was placed in the middle of the low pressure chamber and the high pressure chamber, with an effective area of 3.14 cm 2 As the pressure in the high pressure chamber increases, the flux-pressure curve of the membrane can be obtained. The gas permeability is calculated using the formula F = Q / (A×P), where A and P are the test area and pressure, respectively.
[0054] The nanoporous graphene separation membrane has no water permeation at a pressure of 5 bar, indicating that within the pressure range of 0-5 bar, the graphene layer can block liquid water. The water vapor permeability of the nanoporous graphene composite membrane is 129.3 gm -2 d -1 The gas permeability of the nanoporous graphene separation membrane is 23.0 L m in the pressure range of 0-5 bar. -2 d -1 Pa -1 The reinforced composite membrane still maintains the advantages of graphene in separation performance, has excellent gas permeability, and has a low water vapor transmission rate, and has great potential in waterproof and breathable applications.
[0055] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A two-dimensional thin film material composite film, characterized in that: It includes stacked two-dimensional material films, bonding layers and reinforcement layers.
2. A method for preparing a two-dimensional thin film material composite film, characterized in that: include: S1, forming a bonding layer on the surface of the two-dimensional material film grown on the substrate to obtain a bonding layer / two-dimensional material film / substrate composite structure; S2, compounding a reinforcing layer on the bonding layer of the bonding layer / two-dimensional material film / substrate composite structure to obtain a reinforcing layer / bonding layer / two-dimensional material film / substrate composite structure; as well as S3, removing the substrate in the reinforcing layer / binding layer / two-dimensional material film / substrate composite structure to obtain the two-dimensional thin film material composite film.
3. Use of the two-dimensional thin film material composite membrane according to claim 1 as a separation membrane.